Influence of the Heat Treatment on the Microstructure, Mechanical Properties and Fatigue Behavior of Additively Manufactured Ti6Al4V Alloy - Frkan, Martin; Konecna, Radomila; Nicoletto, Gianni (Communications - Scientific letters of the University of Zilina, 2018)
This contribution deals with the selective laser melting (SLM), which is one of the additive manufacturing (AM) technologies enabling the production of complex parts from metal powder, layer-by-layer wise. This technology uses laser as source of energy to melt a powder to compact state. Properties of final products can be significantly influenced by the process parameters and post-fabricated heat treatments. The purpose of this study is to determine the effect of a heat treatment on properties of the Ti6Al4V alloy specimens manufactured by Eosint M280 machine by the SLM. Three sets of specimens, treated at different temperatures (730 ˚C, 900 ˚C, 1200 ˚C), resulting in a different structure, associated mechanical and fatigue properties, were investigated.